Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
#)Giải :
Bài 1 :
a) \(P=\left(\frac{\sqrt{x}-2}{x-1}-\frac{\sqrt{x}+2}{x+2\sqrt{x}+1}\right)\left(\frac{1-x}{\sqrt{2}}\right)^2\)
\(=\left[\frac{\left(\sqrt{x}-2\right)\left(\sqrt{x}+1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)^2}-\frac{\left(\sqrt{x}+2\right)\left(\sqrt{x}-1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)^2}\right]\frac{\left(1-x\right)^2}{2}\)
\(=\frac{x-\sqrt{x}-2-x-\sqrt{x}+2}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)^2}.\frac{\left(\sqrt{x}-1\right)^2\left(\sqrt{x+1}\right)^2}{2}\)
\(=\frac{-2\sqrt{x}}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)^2}.\frac{\left(\sqrt{x}-1\right)^2\left(\sqrt{x}+1\right)^2}{2}\)
\(=-\sqrt{x}\left(\sqrt{x}-1\right)\)
b) Để \(P>0\Rightarrow\hept{\begin{cases}\sqrt{x}>0\\1-\sqrt{x}>0\end{cases}\Rightarrow0< x< 1}\)
c) \(P=-x+\sqrt{x}=-\left(x-2\sqrt{x}.\frac{1}{2}+\frac{1}{4}\right)+\frac{1}{4}=-\left(\sqrt{x}-\frac{1}{2}\right)^2+\frac{1}{4}\le\frac{1}{4}\)
Dấu ''='' xảy ra khi \(x=\frac{1}{4}\)
ĐKXĐ: x \(\ge\)0; x \(\ne\)1
a) P = \(\left(\frac{2}{\sqrt{x}-1}-\frac{5}{x+\sqrt{x}-2}\right):\left(1+\frac{3-x}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\right)\)
P = \(\left(\frac{2\left(\sqrt{x}+2\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}-\frac{5}{x+2\sqrt{x}-\sqrt{x}-2}\right):\frac{x+\sqrt{x}-2+3-x}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)
P = \(\frac{2\sqrt{x}+4-5}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\cdot\frac{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}{\sqrt{x}+1}\)
P = \(\frac{2\sqrt{x}+1}{\sqrt{x}+1}\)
b) P = \(\frac{1}{\sqrt{x}}\) <=> \(\frac{2\sqrt{x}+1}{\sqrt{x}+1}=\frac{1}{\sqrt{x}}\)
=> \(\sqrt{x}\left(2\sqrt{x}+1\right)-\sqrt{x}-1=0\)
<=> \(2x+\sqrt{x}-\sqrt{x}-1=0\)
<=> \(x=\frac{1}{2}\)(tm)
c)Với đk: x \(\ge\)0 và x \(\ne\)1
\(x-2\sqrt{x-1}=0\) (đk: \(x\ge1\))
<=> \(x-1-2\sqrt{x-1}+1=0\)
<=> \(\left(\sqrt{x-1}-1\right)^2=0\)
<=> \(\sqrt{x-1}-1=0\)
<=> \(\sqrt{x-1}=1\)
<=> \(\left(\sqrt{x-1}\right)^2=1\)
<=> \(\left|x-1\right|=1\)
<=> \(\orbr{\begin{cases}x=0\left(ktm\right)\\x=2\left(tm\right)\end{cases}}\)
Với x = 2 => P = \(\frac{2\sqrt{2}+1}{\sqrt{2}+1}=\frac{\left(2\sqrt{2}+1\right)\left(\sqrt{2}-1\right)}{\left(\sqrt{2}-1\right)\left(\sqrt{2}+1\right)}=\frac{4-2\sqrt{2}+\sqrt{2}-1}{2-1}=3-\sqrt{2}\)
a) P = \(\frac{2\sqrt{x}-1}{\sqrt{x}+1}\)(sửa lại)
b) \(\frac{2\sqrt{x}-1}{\sqrt{x}+1}=\frac{1}{\sqrt{x}}\) => \(2x-\sqrt{x}-\sqrt{x}-1=0\)
<=> \(2x-2\sqrt{x}-1=0\)<=> \(2\left(x-\sqrt{x}+\frac{1}{4}\right)-\frac{3}{4}=0\)
<=> \(2\left(\sqrt{x}-\frac{1}{2}\right)^2=\frac{3}{4}\) <=> \(\left(\sqrt{x}-\frac{1}{2}\right)^2=\frac{3}{8}\)....(tiếp tự lm)
a: \(A=\dfrac{\left(\sqrt{a}-\sqrt{b}\right)^2}{\sqrt{a}-\sqrt{b}}-\dfrac{\sqrt{ab}\left(\sqrt{a}+\sqrt{b}\right)}{\sqrt{ab}}\)
\(=\sqrt{a}-\sqrt{b}-\sqrt{a}-\sqrt{b}=-2\sqrt{b}\)
b: \(B=\dfrac{2\sqrt{x}-x-x-\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}\cdot\dfrac{x+\sqrt{x}+1}{x-1}\)
\(=\dfrac{-2x+\sqrt{x}-1}{\sqrt{x}-1}\cdot\dfrac{1}{x-1}\)
c: \(C=\dfrac{x-9-x+3\sqrt{x}}{x-9}:\left(\dfrac{3-\sqrt{x}}{\sqrt{x}-2}+\dfrac{\sqrt{x}-2}{\sqrt{x}+3}+\dfrac{x-9}{x+\sqrt{x}-6}\right)\)
\(=\dfrac{3\left(\sqrt{x}-3\right)}{x-9}:\dfrac{9-x+x-4\sqrt{x}+4+x-9}{\left(\sqrt{x}+3\right)\left(\sqrt{x}-2\right)}\)
\(=\dfrac{3}{\sqrt{x}+3}\cdot\dfrac{\left(\sqrt{x}+3\right)\left(\sqrt{x}-2\right)}{x-4\sqrt{x}+4}\)
\(=\dfrac{3}{\sqrt{x}-2}\)
\(P=\left(\frac{1}{x-\sqrt{x}}-\frac{1}{\sqrt{x}-1}\right).\frac{x-2\sqrt{x}+1}{\sqrt{x}-1}\)
\(=\left(\frac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}-\frac{1}{\sqrt{x}-1}\right).\frac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}-1}\)
\(=\left(\frac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}-\frac{1}{\sqrt{x}-1}\right).\left(\sqrt{x}-1\right)\)
\(=\frac{1}{\sqrt{x}-1}\)
Để \(P< \sqrt{P}\)
\(\Rightarrow\hept{\begin{cases}P\ge0\\P^2< P\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}P\ge0\\P^2-P< 0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}P\ge0\\P\left(P-1\right)< 0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}P\ge0\\0< P< 1\end{cases}}\)
\(\Rightarrow0< P< 1\)
+ ) \(P>0\Rightarrow\frac{1}{\sqrt{x}}-1>0\Rightarrow\frac{1}{\sqrt{x}}>1\)
\(\Rightarrow\sqrt{x}< 1\Rightarrow0< x< 1\)
+ \(P< 1\Rightarrow\frac{1}{\sqrt{x}-1}< 1\Rightarrow\frac{1}{\sqrt{x}}< 2\)
\(\Rightarrow\sqrt{x}>\frac{1}{2}\Rightarrow x>\frac{1}{4}\)
\(\Rightarrow\frac{1}{4}< x< 1\)